2023
DOI: 10.1021/acs.joc.3c01072
|View full text |Cite
|
Sign up to set email alerts
|

Decarboxylative Cross-Electrophile Coupling of (Hetero)Aromatic Bromides and NHP Esters

Ethan M. DeCicco,
Simon Berritt,
Thomas Knauber
et al.

Abstract: Aryl bromides are known to be challenging substrates in the decarboxylative cross-electrophile coupling with redoxactive NHP esters−the majority of such processes utilize aryl iodides. Herein, we describe the development of conditions that are suitable for the decarboxylative cross-electrophile coupling of NHP esters and a wide range of (hetero)aryl bromides. The key advances that allowed for the use of aryl bromides in this reaction are (1) the identification of ligand L3 as an optimal ligand for the use of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…To the best of our knowledge, these are some of the highest yields for C­(sp 2 )–C­(sp 3 ) XEC reactions reported for 2-haloazines under similar conditions. We could find only a single example of the coupling of S8 with an alkyl N -hydroxyphthalimide ester using 20 mol % nickel and no examples of couplings with S10 – S12 . …”
Section: Resultsmentioning
confidence: 96%
“…To the best of our knowledge, these are some of the highest yields for C­(sp 2 )–C­(sp 3 ) XEC reactions reported for 2-haloazines under similar conditions. We could find only a single example of the coupling of S8 with an alkyl N -hydroxyphthalimide ester using 20 mol % nickel and no examples of couplings with S10 – S12 . …”
Section: Resultsmentioning
confidence: 96%
“…We found that L5 enables higher yields than L2 in the decarboxylative arylation of an N -hydroxyphthalimide ester with an aryl bromide (Table and Figure S4.12). Notably, the coupling of redox-active esters with bromoarenes often requires the use of carboxamidine-based ligands to enable high conversion and selectivity. These results suggest that L5 may be widely useful in coupling a variety of electrophiles. Indeed, we were also able to directly substitute L5 for L2 in the reported coupling of N -alkyl 2,4,6-triphenylpyridiniums with aryl bromides (Table ).…”
Section: Resultsmentioning
confidence: 99%